The Effect of Antihypertensive Medications on Testing for Primary Aldosteronism - Jędrusik, Piotr; Symonides, Bartosz; Lewandowski, Jacek; Gaciong, Zbigniew (Frontiers in Pharmacology, 2021)
Primary aldosteronism (PA) is a potentially curable form of secondary hypertension caused by excessive renin-independent aldosterone secretion, leading to increased target organ damage and cardiovascular morbidity and mortality. The diagnosis of PA requires measuring renin and aldosterone to calculate the aldosterone-to-renin ratio, followed by confirmatory tests to demonstrate renin-independent aldosterone secretion and/or PA subtype differentiation. Various antihypertensive drug classes interfere with the renin-angiotensin-aldosterone axis and hence evaluation for PA should ideally be performed off-drugs. This is, however, often precluded by the risks related to suboptimal control of blood pressure and serum potassium level in the evaluation period. In the present review, we summarized the evidence regarding the effect of various antihypertensive drug classes on biochemical testing for PA, and critically appraised the issue whether and which antihypertensive medications should be withdrawn or, conversely, might be continued in patients evaluated for PA. The least interfering drugs are calcium antagonists, alpha-blockers, hydralazine, and possibly moxonidine. If necessary, the testing may also be attempted during treatment with beta-blockers, angiotensin-converting enzyme inhibitors, and angiotensin receptor blockers but renin and aldosterone measurements must be interpreted in the context of known effects of these drugs on these parameters. Views are evolving on the feasibility of testing during treatment with mineralocorticoid receptor antagonists, as these drugs are now increasingly considered acceptable in specific patient subsets, particularly in those with severe hypokalemia and/or poor blood pressure control on alternative treatment.